Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1088/0953-8984/27/49/495101
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of annealed branched polymers on curved surfaces

Abstract: The behavior of annealed branched polymers near adsorbing surfaces plays a fundamental role in many biological and industrial processes. Most importantly single stranded RNA in solution tends to fold up and self-bind to form a highly branched structure. Using a mean field theory, we both perturbatively and numerically examine the adsorption of branched polymers on surfaces of several different geometries in a good solvent. Independent of the geometry of the wall, we observe that as branching density increases,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…A detailed derivation of Eq. 2 is given in [45]. In this model, the stem-loop or hair-pin configurations of RNA are counted as the end points.…”
Section: Modelmentioning
confidence: 99%
“…A detailed derivation of Eq. 2 is given in [45]. In this model, the stem-loop or hair-pin configurations of RNA are counted as the end points.…”
Section: Modelmentioning
confidence: 99%
“…A closer inspection of micrographs from individual particles revealed that native immature HIV‐1 particles differ from each other with respect to their local curvature, average radius, and protein coverage at budding, suggesting that each particle really possessed its own unique topology. From theoretical studies of icosahedral virus models and spherical packings of interacting isotropic subunits, it is clear that curvature plays a major role in thermodynamic stability and the geometry of the ground state . However, the relationship between the geometry of immature HIV‐1 and its stability and, subsequently, virus infectivity is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…where and are the fugacities of the end and branched points of the annealed chain, respectively (54) and is the effective excluded volume of each monomer. It is worth mentioning that in this model, the stem-loop or hair-pin configurations of RNA are considered as end points.…”
Section: Numerical Calculationsmentioning
confidence: 99%